Direct and indirect effects of planting density, nitrogenous fertilizer and host plant resistance on rice herbivores and their natural enemies - Horgan, Finbarr G.; Crisol-Martínez, Eduardo; Stuart, Alexander M.; Villegas, James M.; Peñalver-Cruz, Ainara; Mundaca, Enrique A.; Perez, Marivic O.; Bernal, Carmencita C.; Almazan, Maria Liberty P.; Ramal, Angelee F. (MDPI, 2022)
In rice ecosystems, seeding densities can be adjusted to compensate for lower nitrogen levels that reduce GHG emissions, or to increase farm profitability. However, density-induced changes to plant anatomy could affect herbivore-rice interactions, and alter arthropod community dynamics. We conducted an experiment that varied transplanting density (low or high), nitrogenous fertilizer (0, 60 or 150 kg added ha−1) and rice variety (resistant or susceptible to phloem-feeding insects) over two rice-growing seasons. Yields per plot increased with added nitrogen, but were not affected by variety or transplanting density. Planthopper and leafhopper densities were lower on resistant rice and in high-density field plots. Nitrogen was associated with higher densities of planthoppers, but lower densities of leafhoppers per plot. High planting densities and high nitrogen also increased rodent damage. The structure of arthropod herbivore communities was largely determined by season and transplanting density. Furthermore, two abundant planthoppers (Sogatella furcifera (Horváth) and Nilaparvata lugens (Stål)) segregated to low and high-density plots, respectively. The structure of decomposer communities was determined by season and fertilizer regime; total decomposer abundance increased in high-nitrogen plots during the dry season. Predator community structure was determined by season and total prey abundance (including decomposers) with several spider species dominating in plots with high prey abundance during the wet season. Our results indicate how rice plasticity and arthropod biodiversity promote stability and resilience in rice ecosystems. We recommend that conservation biological control, which includes a reduction or elimination of insecticides, could be promoted to attain sustainable rice production systems.